Per la costruzione di un pluralismo sostenibile nel rapporto tra diritto e scienze della vita (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The law focusing on life sciences and on human health is characterised by significant tensions that oppose the need for unity and certainty of the legal order, on the one hand, and pressures for the acknowledgement of different moral values and visions, on the other hand. It is also a field in which the speed of scientific development continuously requires law-makers and judges to “adapt” the legal framework to new needs and possibilities.Given this context, the paper offers an analysis of the relationship between legislation and jurisdiction organised into three main categories, in which the starting point is represented by the legislative approach. Depending on the level of “rigidity” or “flexibility” of the legislation with respect to the acknowledgement of individual moral values and to the integration of the scientific dimension at a normative level, the role of jurisdiction might significantly vary. In a scheme in which the law-maker tends to deny or refuse pluralism, the jurisdiction is called to guarantee the necessary equilibrium among the different components of the society. Differently, in the case of a “inactive” law-maker (second category), judicial interventions are fundamental in giving an answer to needs and issues arising at a scientific and social level in the absence of a specific regulation. Finally, even if the different levels of pluralisms find legislative protection, courts might open the way to new rights or new individual position that deserve protection by the legal order.The aim of the paper is to identify the main features of a sustainable model of pluralism, in which both law-makers and judges contribute together to the equal guarantee of constitutionally relevant values and in which the legal order is able to constantly keep the pace with scientific development.
Keywords: Pluralisms; Jurisdiction; Moral values; Scientific development; Biolaw